Beyond surface correlations: Reference behavior mediates the disruptiveness-citation relationship - Yang Alex J.; Wang Fanming; Shi Yujie; Zhang Yiqin; Wang Hao; Deng Sanhong (Journal of Data and Information Science, 2025)
This study examines why papers with high CD indices (measuring research disruptiveness) increasingly show reduced citation impact and investigates whether this represents genuine impact reduction or methodological artifacts.